1999
DOI: 10.1359/jbmr.1999.14.10.1714
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Neck Length and Hip Fracture Risk

Abstract: To determine whether there are differences in femoral skeletal geometry in fracture-prone subjects when size, positioning diagnosis, and age are controlled, we compared femoral measurements made from the uninvolved hip on 119 plane anteroposterior pelvis radiographs of women without fracture to those of the contralateral hip in a group of 43 female patients with hip fractures (neck, 23; intertrochanteric, 20). The hip was imaged in a standardized position of rotation and adduction. Race, age, and musculoskelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
66
4
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 27 publications
4
66
4
2
Order By: Relevance
“…It is difficult to maintain a good positioning of the hip joint so as to be able to analyze the geometry using such techniques as HAL and NSA in the radiographs and DXA after hip fracture, since the legs are usually abducted and outwardly rotated 18) . If the measurement is performed after an operation, the parameters are influenced by the effect of limb disuse.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to maintain a good positioning of the hip joint so as to be able to analyze the geometry using such techniques as HAL and NSA in the radiographs and DXA after hip fracture, since the legs are usually abducted and outwardly rotated 18) . If the measurement is performed after an operation, the parameters are influenced by the effect of limb disuse.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data suggest that weakened cortical bone may primarily be responsible for hip intracapsular hip fracture (6), thus emphasizing the importance for quantitatively assessing and monitoring cortical structure. Support for the role of cortical bone architecture as a risk factor for hip fracture is found in several studies of postmenpausal osteoporosis, where strong associations have been reported between proximal femur geometry and fracture incidence (7)(8)(9). Additionally, bone mineral density (BMD) supplemented by femoral geometry has been shown to be more predictive of breaking strength than BMD alone (10).…”
Section: Introductionmentioning
confidence: 98%
“…Thus, proximal femora of elderly men and women with any type of osteoporotic fracture have lower estimated bending strength and axial strength, thinner cortices and wider subperiosteal diameters than femora of fracturefree counterparts [8]. Compared to those without fractures, women with hip fractures (as well as their daughters [8,9]) have altered femoral geometry, including wider femoral necks and longer hip axis lengths, independently of femoral neck BMD, age, and body size [10][11][12][13][14][15][16]. Currently, femoral geometry is assessed non-invasively by radiogrammetry and/or DXA-based hip structural analysis (HSA), as well as by 3D methods like computed tomography.…”
Section: Introductionmentioning
confidence: 99%